Toxicidade dos metais cádmio, cobalto e níquel, isolados e em combinações binárias, para a clorofícea Raphidocelis subcapitata - Reis, Larissa Luiza dos (2023)
In aquatic ecosystems, organisms are exposed to several compounds capable of interacting and generating toxic effects. Metals are naturally present in these environments and some are essential to the metabolism of organisms. However, anthropic activities have increased the concentration of these elements, which are capable of causing damage from the first trophic level. In the present study, the effects of the metals cadmium (Cd), cobalt (Co) and nickel (Ni), isolated and in binary combinations, on density, maximum quantum yield (ΦM), efficiency of the oxygen evolution complex (F0 /Fv), generation of reactive oxygen species (ROS), carbohydrate synthesis, chlorophyll a fluorescence, cell size and complexity of the freshwater chlorophyte Raphidocelis subcapitata. Cd decreased cell density, ΦM, increased ROS generation, F0/Fv, chlorophyll a fluorescence, size and cell complexity. Co decreased density, chlorophyll a fluorescence, carbohydrate synthesis, and ΦM and, on the other hand, increased ROS, F0/Fv, size and the cellular complexity. Ni caused changes (increase and decrease) in cell density and in ROS generation, decreased carbohydrate synthesis, and chlorophyll a fluorescence. Regarding the photosynthetic parameters, Ni did not alter ΦM and caused an increase in F0/Fv only at 0.50 mg L-1. The Cd-Co mixture caused synergistic effects at high doses of Co and low doses of Cd; and antagonism at low Co and high Cd concentrations. The model that best fitted the data was CA (concentration addition) with DR deviation (dependent on the dose ratio). Furthermore, the mixture caused antagonistic effects to ΦM and F0/Fv. The Cd-Ni mixture, on the other hand, resulted in antagonism effects at low doses and synergism at high doses, with a dose level change greater than IC50. The IA model (independent action) with DL deviation (dose level dependent) best explained the data. Photosynthetic parameters were not altered by the mixture of metals, however, there was an increase in cell size and complexity, as well as changes in ROS generation and chlorophyll a fluorescence. And the Co-Ni mixture resulted in synergistic effects at low Co and high Ni doses and antagonism at high Co and low Ni doses, the data better fit the CA model with DR deviation, with changes in all analyzed parameters. Considering that microalgae are the basis of aquatic food webs and metals can be bioaccumulated and biomagnified, the damage caused can reach higher trophic levels and impact the ecosystem. Therefore, it is concluded that the metal mixtures caused toxicity to the microalgae, highlighting the importance of evaluating the studies of mixtures, their effects and mechanisms of toxicity on the organisms, in order to protect the biodiversity of the aquatic ecosystem.